2020
DOI: 10.1016/j.cobeha.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Is early good or bad? Early puberty onset and its consequences for learning

Abstract: Entering puberty at a relatively young age is often thought to be associated with negative outcomes, such as poorer cardiovascular and psychosocial health. However, the literature on the relationship between early puberty, learning and academic achievement is inconclusive. Previous work suggests both positive and negative outcomes of early puberty. We here review recent findings on the relationship between early puberty and cognitive outcomes and integrate these findings into larger theoretical frameworks of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
(62 reference statements)
0
12
2
Order By: Relevance
“…On both inhibition and working memory, a temporarily lower score is seen for earlier maturing adolescents. This could possibly be due to the reorganization of the prefrontal cortex, induced by sex hormones (Chaku and Hoyt, 2019;Laube and Fuhrmann, 2020), although the temporary decline in performance should eventually emerge in all adolescents at some chronological age, when puberty onset starts, a general temporary decline in score was not observed in this study. The maturation disparity hypothesis can explain why the short decrease in scores could potentially only happen to earlier maturing adolescents, because they might encounter more challenges at puberty onset than their peers, resulting in different EF scores during adolescence FIGURE 3 | Prediction plots based on the interaction between age and %PAH in GEE model 3 per sex (A = male, B = female), for each EF component (1 = Inhibition, 2 = Planning, 3 = Shifting, 4 = Working memory).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…On both inhibition and working memory, a temporarily lower score is seen for earlier maturing adolescents. This could possibly be due to the reorganization of the prefrontal cortex, induced by sex hormones (Chaku and Hoyt, 2019;Laube and Fuhrmann, 2020), although the temporary decline in performance should eventually emerge in all adolescents at some chronological age, when puberty onset starts, a general temporary decline in score was not observed in this study. The maturation disparity hypothesis can explain why the short decrease in scores could potentially only happen to earlier maturing adolescents, because they might encounter more challenges at puberty onset than their peers, resulting in different EF scores during adolescence FIGURE 3 | Prediction plots based on the interaction between age and %PAH in GEE model 3 per sex (A = male, B = female), for each EF component (1 = Inhibition, 2 = Planning, 3 = Shifting, 4 = Working memory).…”
Section: Discussioncontrasting
confidence: 53%
“…%PAH, percentage of predicted adult height. (Ge and Natsuaki, 2009;Laube and Fuhrmann, 2020). We should also take into account that females have a 2-year head start in their biological maturation process compared to males (Malina et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developmental theories suggest that early puberty may accentuate preexisting differences in childhood (Caspi & Moffitt, 1991) or impair plasticity and learning (Schulz et al, 2009). Note, however, that several empirical (Chaku & Hoyt, 2019;Koerselman & Pekkarinen, 2017) and theoretical studies (Belsky et al, 2007;Laube & Fuhrmann, 2020) now suggest that in supportive environments, early puberty can be linked to more positive cognitive outcomes, too. Chaku and Hoyt (2019) showed that early maturation may be associated with lower self-control but also better attention.…”
Section: Risk and Resilience Factors Explain Heterogeneity In Trajectoriesmentioning
confidence: 99%